Food systems in conflict-prone and climate-affected areas of Northern Nigeria: Humanitarian and development challenges - Balana, Bedru; Omamo, Steven Were; Amare, Mulubrhan; Popoola, Olufemi; Nwagboso, Chibuzo; Iraoya, Augustine Okhale; Loum, Serigne; Jawed, Khusro; Andam, Kwaw S. (International Food Policy Research Institute, 2025)
Protracted conflict and climate shocks have profoundly disrupted food systems in northern Nigeria, yet little empirical evidence exists on how these shocks shape the functioning of the region’s food system (production, transportation, value addition, and trade). This study addresses this evidence gap by combining GIS-based mapping, cost structure analysis, and investment opportunities in food production, transportation, processing, and trade in key staple commodities across conflict-prone and climate-affected areas of northern Nigeria and connected market hubs. The analysis quantifies cost structures for key food supply chain actors, identifies systemic food system inefficiencies driven by conflict and climate factors, and examines how these factors undermine both commercial and humanitarian food flows. By integrating commodity-specific diagnostics with stakeholder perspectives, the study offers an evidence-based rationale for prioritizing interventions in conflict contexts. Two investment cases—on-farm storage and localized wheat milling—illustrate how targeted actions can reduce losses, enhance resilience, and create co-benefits for humanitarian operations and market recovery. By combining food-flow maps and cost structures for multiple actors along the food supply chain in a high-risk environment, and by demonstrating simplified approaches to linking empirical diagnostics with practical investment strategies, the study’s findings contribute to the literature on the functioning of food systems in conflict-prone and climate-affected contexts. In addition, the findings provide evidence to support policy changes, interventions, and investment decisions aimed at transforming food systems and addressing structural failures, while enhancing the efficacy of short-term humanitarian interventions. They also address the underlying causes of chronic food insecurity and support economic recovery in the region.